Radio: the weather wavelength - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Recent advances in meteorology mean that radio is set to become one of the prime tools in communicating weather forecasts to rural dwellers. Sahelian agriculture is very much at the mercy of the weather. The average annual rainfall is between 30 and...